From Local Invasion to Metastatic Cancer Involvement of Distant Sites Through the Lymphovascular System - Leong, Stanley P. L. (Current Clinical Oncology,, 2009)
In human solid tumors, nodal status is the most important prognostic indicator for patient outcome. Recent developments in the sentinel lymph node concept have resulted in new procedures to define the first draining node as the primary gateway through which the cancer will spread. In From Local Invasion to Metastatic Cancer: Involvement of Distant Sites Through the Lymphovascular System, a panel of international authorities takes an in-depth look at the role of the lymphovascular system in the spread of cancer. The authors summarize the findings of the Second International Symposium on Cancer Metastasis: Basis for Rational Therapy summit. Specifically, the book presents important developments in the biology and clinical understanding of cancer metastasis, describes the relationship between tumor microenvironment and proliferation, and defines the process of lymphangiogenesis and angiogenesis with special reference to cancer metastasis. From Local Invasion to Metastatic Cancer: Involvement of Distant Sites Through the Lymphovascular System provides oncologists, radiologists, and cancer researchers the necessary information to study and develop new strategies to curb the process of metastasis.